The analysis of agro-economic effects of household food wastage through the example of bread - Hubert , Klára; Szűcs , István (Applied Studies in Agribusiness and Commerce, 2017)
In our busy world, where numerous people starve and where the resources are restricted, it is a key issue to pay particular attention to the topic of prevention and decrease of food loss as well as food wastage.Wastage of food produced and delivered to the end user (customer) is an issue arising globally and nationally as well, which results in efficiency loss at economic level in any case. While the FAO study mentions food waste of the order of 1.3 billion tonnes on a world scale, then the annual quantity of food waste in Hungary is estimated at about 1.8 million tonnes, which contains the waste of every member of the chain from production to consumption. On the basis of the data published by the Hungarian Food Bank (2015), the amount of food waste caused by the population is 400 000 tonnes. In compliance with our objectives, inputs – expressed by non-financial and financial indicators – emerge during production are assigned to the quantity of wasted food. Applying the aforementioned method we would like to make customers realize how many resources (land, water, artificial fertilizer, pesticide, seed and gasoil) are utilized needlessly in food verticum by the end products – at present by different breads they throw out. As our calculations prove by 10% waste of breads the utilization of 5 300 hectares of wheat land and 660 hectares of rye land can be considered unnecessary. By 10% waste of breads the financial value of the utilized resources is altogether 3.25 million EUR. Out of this the financial value of utilized artificial fertilizer is 1.10 million EUR (34%), of utilized pesticide is 1.15 million EUR (35%), of utilized gasoil is 0.70 million EUR (22%) and of utilized seed is 0.30 million EUR (9%). Among different breads, white bread is purchased in the greatest volume by the Hungarian households, from which 121 900 tonnes are bought annually on an average. This quantity is equal to almost the 40% of the annual bread sell. If 10% of purchased white bread is thrown out, it results in useless utilization of 2 676 hectares of wheat land in food verticum. The quantity of utilized water arising form wastage is 15.8 million m3. Further losses emerge as regards material inputs: artificial fertilizer- to the value of 0.50 million EUR, pesticide- to the value of 0.58 million EUR, seed to the value of 0.15 million EUR and gasoil-loss to the value of circa 0.35 million EUR. Totally, material input to the value of 1.58 million EUR is owing to the Hungarian households in case of 10% white bread wastage.JEL code: Q53